2019
DOI: 10.1180/mgm.2019.68
|View full text |Cite
|
Sign up to set email alerts
|

Majzlanite, K2Na(ZnNa)Ca(SO4)4, a new anhydrous sulfate mineral with complex cation substitutions from Tolbachik volcano

Abstract: A new mineral majzlanite, ideally K2Na(ZnNa)Ca(SO4)4, was found in high-temperature exhalative mineral assemblages in the Yadovitaya fumarole, Second scoria cone of the Great Tolbachik Fissure Eruption (1975–1976), Tolbachik volcano, Kamchatka Peninsula, Russia. Majzlanite is associated closely with langbeinite and K-bearing thénardite. Majzlanite is grey with a bluish tint, has a white streak and vitreous lustre. The mineral is soluble in warm water. Majzlanite is monoclinic, C2/c, a = 16.007(2), b = 9.5239(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…The same is true for K-Cu pair, which is only confirmed in channels of aleutite [54]. A (Zn,Na,Cu,Mg) diadochy is also known in majzlanite [55]. Nevertheless, possible Na-Cu and K-Cu substitution systems in our minerals need further studies to be confirmed or disproved.…”
Section: supporting
confidence: 60%
“…The same is true for K-Cu pair, which is only confirmed in channels of aleutite [54]. A (Zn,Na,Cu,Mg) diadochy is also known in majzlanite [55]. Nevertheless, possible Na-Cu and K-Cu substitution systems in our minerals need further studies to be confirmed or disproved.…”
Section: supporting
confidence: 60%
“…A similarly short Cu-S distance of 2.593 Å is observed in chlorothionite, K 2 CuCl 2 (SO 4 ) (Giacovazzo et al, 1976) wherein the CuO 6 octahedron shares an edge with a SO 4 group. Edge sharing has also been recently observed in the complex Zn sulfate majzlanite, K 2 Na(ZnNa)Ca(SO 4 ) 4 (Siidra et al, 2020), with a Zn-S distance of 2.8704(4) Å.…”
Section: Rb 2 Cu(so 4 )mentioning
confidence: 67%
“…A zinc admixture is very common for many exhalative Cu sulfate minerals (Pekov et al ., 2018b). Surprisingly, until recently (Siidra et al ., 2018a,b; Siidra et al ., 2020), no anhydrous sulfate minerals with Zn-dominated sites in the structure were known and the occurrence of zinkosite, ZnSO 4 , is doubtful to date (Wildner and Giester, 1988).…”
Section: Introductionmentioning
confidence: 99%